Efektivitas Model Problem Based Learning Berbantuan Media Educomic terhadap Hasil Belajar IPAS - Ramadhani, Naisya; Kironoratri, Lintang; Masfuah, Siti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study is motivated by the low learning outcomes of IPAS which based on the observation results of 20 students show that only 40% of students with high learning outcomes, with an average score of 65, far below the set KKTP standard (75). This study examines the effectiveness of the Problem Based Learning (PBL) model assisted by educomic media on the learning outcomes of social studies as a dependent variable. The PBL model is a series of learning that focuses on solving problems in daily life. This study uses a quantitative method with a pre-experimental design of the type one-group, pre-test, and post-test. Data were collected through interviews, observations, and written tests in the form of descriptions. Data analysis was carried out using Statistical Product and Service Solutions (SPSS) version 27, starting with a normality test using the Shapiro-Wilk technique, then continued with the N-gain test. The results of the study showed the effectiveness of the application of the PBL model assisted by educomic media on the learning outcomes of IPAS. This is evidenced by the N-gain test value of 0.52 which is in the range of 0.3 ≤ g < 0.7 so it is categorized as a moderate increase.